(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Indians are extoled worldwide for their high principles and erudite. The success of Indian writers has reached such an extent that woman authors are also breaking into the field in a major way and making us proud with their wonderful writings. Anita Desai is one them who with her keen blade of writing makes Indian fiction in English gain distinction in discovering the social essence and the emotional spirits of her protagonists. She is a keen observer of the society and tries to retain the position of the women in the contemporary society attracting attention of the masses through her writings. This paper is an important insight of feminine perspective in the novel Clear Light of Day by Anita Desai, while exploring feminism in Indian Writings in English. At the same time, efforts have been done how various women characters play different roles and emerge out as new identity to overcome the situation.